Topics in measurement. (1995)
The paper aims of studying measures of the state of an economy which were intended to be independent of welfare criteria.
1. Introduction -- 2. Measurement of income -- 3. Equivalence scales -- 4. the measurement of inequality -- 5. The measurement of poverty -- 6. Conclusions.
Photocopy.
Source: Myles, Gareth D. 1995. Public Economics. Cambribge: Cambridge University Press, p. 59-96.
Keywords: Educational tests and measurements; Public welfare; Welfare economics